The synonymization of Philodice with Syngonanthus (Eriocaulaceae) - Giulietti, Ana Maria; Hensold, Nancy; Parra, Lara Regina; de Andrade, Maria José Gomes; Berg, Cassio Van Den; Harley, Raymond Mervyn (Phytotaxa, 2012)
Philodice hoffmannseggii and P. cuyabensis, the only species in this genus, are here recognized as a single species and transferred to the genus Syngonanthus as S. cuyabensis. The taxonomic history and morphology of Philodice are reviewed, and infraspecific variation, and affinities within Syngonanthus are discussed.